Second-order aperiodic link modelling with the use of Siemens programmable logical controller SCL hardware. (November 2020) - Urasov, D; Cherniy, S; Bazhenov, R; Alekseeva, L; Korosteleva, I
Abstract: The paper focuses on the features of modelling the elements of control systems using non-standard tools, in particular, based on the resources provided by industrial logic controllers. The authors point out the features of implementing such models, the control program for an industrial logical controller, as well as the forwarding algorithm for control data to regular simulation modelling tools. A comparative study of the obtained properties with models built in the environment of engineering computing proved to be appropriate to use such hardware and software to solve problems of that kind.